QUALITY OF BOAR SEMEN EXTENDED IN PALM WATER-EGG YOLK DILUENT SUPPLEMENTED WITH A. DORSATA AND TRIGONA SP. HONEY - Maria Patrisila Naibina; Wayan Bebas; I Gusti Ngurah Bagus Trilaksana; Tjok Gde Oka Pemayun; Desak Nyoman Dewi Indira Laksmi; Ni Nyoman Werdi Susari (Buletin Veteriner Udayana, 2025)
One of the factors that determine the success of artificial insemination in pig livestock is the quality of the semen used. The use of fresh semen without going through the dilution process will result in a decrease in the quality of spermatozoa. This study aims to determine the quality of Landrace pig semen in egg yolk palm water dilution with the addition of Apis dorsata and Trigona Sp. bee honey with a concentration of 3% each. This study used a complete random design pattern with five treatment groups, namely Beltsville Thawing Solution (BTS) diluent as a control (P0), palm fruit water diluent (P1), egg yolk palm water diluent (P2), egg yolk palm water diluent plus A. dorsata honey (P3) and egg yolk palm water diluent plus Trigona Sp. honey (P4). The diluted cement is stored at 150C for 48 hours. The observed semen quality parameters are motility, abnormality, viability, intact plasma membrane and intact acrosome membrane. The results showed that the water semen dilution of egg yolk palm fruit with the addition of A. dorsata honey with a concentration of 3% resulted in the highest motility, viability, intact plasma membrane and intact acrosome membrane and the lowest spermatozoa abnormalities when compared to Trigona Sp. honey and other treatments. It can be concluded that the egg yolk palm fruit water dilutor with the addition of A. dorsata honey with a concentration of 3% is able to maintain the quality of Landrace pig spermatozoa stored at 150C for 48 hours. Therefore, it is necessary to conduct further research on the fertility and litter size of Landrace pigs that are inseminating with egg yolk palm fruit water diluent with the addition of A. dorsata honey with a concentration of 3%.